ANALYSIS OF COMMUNICATION NETWORK IN PINEAPPLE CHIPS AGROINDUSTRY AT KUALU NENAS VILLAGE TAMBANG SUB-DISTRICT KAMPAR DISTRICT - Zaky Syuhada; Roza Yulida; Deby Kurnia (Indonesian Journal of Agricultural Economics, 2021)
Kualu Nenas Village is a pineapple agroindustrial center in the Kualu Nenas Village, Tambang District of Kampar Regency. The development of the pineapple agroindustry in Kualu Nenas Village did not escape the dissemination of information regarding the pineapple chips agroindustry. This information is shared and exchanged by each actor in the network. This study had aimed: (1) analyze the personal and external characteristics of the craftsmen of the pineapple chips agroindustry; (2) analyze communication networks regarding production and marketing in the pineapple chips agroindustry; and (3) analyze the communication network at the actor level in the pineapple chips agroindustry. This research was conducted in Kualu Nenas Village, Tambang District, Kampar Regency. The research was conducted using survey methods and using descriptive analysis and sociometric analysis assisted by the UCINET program. The results showed that the communication network regarding the production and marketing of pineapple chips agroindustry formed an interlocking personal network model. The Restu actor became a star and dominated the centrality in the communication network regarding the production and marketing of the pineapple chips agro-industry in Kualu Nenas Village.